66.0k views
2 votes
2 over 5h - 7 = 12 over 5h-2h+3

User Xi Liang
by
4.8k points

1 Answer

1 vote

To solve this equation you have to clear h


(2)/(5)h-7=(12)/(5)h-2h+3

Pass all h related terms to the left and all other terms to the right of the = sign


(2)/(5)h-(12)/(5)h+2h=3+7

Now you can add/subtract them together


(24)/(5)h=10

Divide by 24/5 to reach the value of h


\begin{gathered} h=(10)/((24)/(4)) \\ h=10\cdot(5)/(24)=(25)/(12) \end{gathered}

h=25/12 or you can express it as a decimal value

h=2.083

User Bheklilr
by
4.6k points